Younger age and female sex predict a better therapeutic response in HBeAg‐positive chronic hepatitis B patients to entecavir therapy. Issue 4 (5th August 2014) - Su, Wei‐Chih; Hsieh, Tsung‐Cheng; Hsieh, Tsai‐Yuan; Tseng, Kuo‐Chih; Peng, Cheng‐Yuan; Lin, Chih‐Lin; Su, Tung‐Hung; Hsiao, Tsung‐Hsien; Tseng, Tai‐Chung; Lin, Hans Hsienhong; Wang, Chia‐Chi; Kao, Jia‐Horng
Summary: Background: Clinical trials and real‐world data confirm the efficacy of entecavir treatment for chronic hepatitis B (CHB); however, the factors associated with a favorable response remain unknown. Methods: In a retrospective multicenter study, 132 treatment‐naïve hepatitis B e antigen (HBeAg)‐positive CHB patients (71% male; median age, 40.2 years) received entecavir therapy for >2 years. At baseline, 15% of these patients had cirrhosis. The primary endpoint was HBeAg loss at 2 years of entecavir treatment. Results: The rates of serum alanine aminotransferase (ALT) normalization at treatment Year 1 and Year 2 were 86% and 88%, respectively. The cumulative rate of HBeAg loss at treatment Year 1 and Year 2 were 17% and 33.3%, respectively. The rates of undetectable levels of serum hepatitis B virus (HBV) deoxyribonucleic acid (DNA) at treatment Year 1 and Year 2 were 64% and 80.8%, respectively. In univariate analysis, HBeAg loss at 2 years was associated with a young age (≤35 years; p  = 0.007) and a high baseline ALT level ( p  < 0.001). Multivariate analysis after adjusting for age, sex, and ALT level [>5 times the upper limit of normal (ULN)] showed that a young age (odds ratio, 2.66; 95% confidence interval, 1.2–5.92) and male sex (odds ratio, 0.36; 95% confidence interval, 0.16–0.83) were independent factors associated with HBeAg loss at 2 years of therapy. Conclusion: Two‐year entecavir therapy has good biochemical and virologic responses; however, the rate of HBeAg loss is modest in HBeAg‐positive CHB patients. A young age (i.e., ≤35 years) and female sex were also associated with a better serologic response.